Industries without smokestacks: Implications for Ethiopia's industrialization - Mulu Gebreeyesus (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Although the manufacturing sector is known to have a unique role in structural transformation, the industries without smokestacks that include tradable services (e.g., IT, tourism, transport), horticulture, and agro-industry can provide new opportunities for export development in low-income countries and in turn drive economic growth. With vast natural and man-made tourist attractions and diversified agroecological advantage, Ethiopia is particularly well positioned to exploit the opportunities in industries without smokestacks. This study takes the case of Ethiopia and examines the current state and contribution of the industries without smokestacks to the economy and exports with the aim of improving our understanding of the major bottlenecks and solutions to unlocking the potential of these industries. It gives special attention to the horticulture and tourism industries, given the huge unexploited potential of these sectors in Ethiopia.
Keywords: F10; L52; L84; N50; 330; Ethiopia; exports; tourism; horticulture